Definition and Classification of Dystonia - Albanese, Alberto; Bhatia, Kailash P.; Fung, Victor S.C.; Hallett, Mark; Jankovic, Joseph; Klein, Christine; Krauss, Joachim K.; Lang, Anthony E.; Mink, Jonathan W.; Pandey, Sanjay; Teller, Jan K.; Tijssen, Marina A.J.; et al. (Movement disorders, 2025)
Dystonia is a movement disorder with varied clinical features and diverse etiologies. Here we present a revision of the 2013 consensus definition and classification of dystonia in light of subsequent publications and experience with its application during the last decade. A panel of movement disorder specialists with expertise in dystonia reviewed the original document and proposed some revision. There was broad consensus to retain the definition of dystonia with only minor clarifications to the wording. Dystonia is defined as a movement disorder characterized by sustained or intermittent abnormal movements, postures, or both. Dystonic movements and postures are typically patterned and repetitive and may be tremulous or jerky. They are often initiated or worsened by voluntary action and frequently associated with overflow movements. The two‐axis structure for classification of the many different presentations of dystonia was also retained, with some revision. Axis I summarizes key clinical characteristics of dystonia, including age at onset, family history, body distribution, temporal dimensions, phenomenology, and whether dystonia is isolated or combined with other neurological or medical problems. Axis II organizes information regarding its etiological basis, including genetic, acquired, and anatomical, and common disease mechanisms. This consensus provides an update to the original definition and classification of dystonia with the aim of facilitating its clinical recognition and management. The revision retains the essence of the original proposal and aims particularly to provide a structure facilitating a uniform implementation. © 2025 The Author(s). Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society.